Neurodegenerative Disease Risk in Carriers of Autosomal Recessive Disease - Vieira, Sophia R. L.; Morris, Huw R. (Frontiers in Neurology, 2021)
Genetics has driven significant discoveries in the field of neurodegenerative diseases (NDDs). An emerging theme in neurodegeneration warrants an urgent and comprehensive update: that carrier status of early-onset autosomal recessive (AR) disease, typically considered benign, is associated with an increased risk of a spectrum of late-onset NDDs. Glucosylceramidase beta (GBA1) gene mutations, responsible for the AR lysosomal storage disorder Gaucher disease, are a prominent example of this principle, having been identified as an important genetic risk factor for Parkinson disease. Genetic analyses have revealed further examples, notably GRN, TREM2, EIF2AK3, and several other LSD and mitochondria function genes. In this Review, we discuss the evidence supporting the strikingly distinct allele-dependent clinical phenotypes observed in carriers of such gene mutations and its impact on the wider field of neurodegeneration.